A study of rubber flow in a mold during the tire shaping process using experiment and computer simulation. (August 2017) - Choi, Sung Hyun; Lyu, Min-Young
Abstract: Automobile tires consist of more than ten layers, including tread, belt, carcass, sidewall, etc. The outermost layer, known as the tread, plays an important role during driving as it comes in direct contact with the road. This tread has grooves with complicated shapes, which are formed by a mold during the shaping process. When the tread rubber does not fill the mold properly, tire quality deteriorates crucially. As such, it is important to observe the flow of the tread rubber during the shaping process. To determine the flow of tread rubber in the mold, we conducted an experiment and computer simulation with white rubber strips inserted into specific areas of the tread. The white rubber strips showed detailed flow behavior of the tread rubber visually in the mold during the shaping process. No significant flows were observed for rubber in the central area of each block of the mold, but more changes were found near the edges of each block. The strips of rubber below the grooves exhibited more significant changes as they were pressed down by the protruding area of the mold. Moreover, there was no flow of rubber between blocks in the mold. This implies the profile design of the extruded tread should match the mold profile and the volume of each block. The experiment and simulation had similar results, and the observations of rubber flow in the mold using simulation proved to be highly useful.